The use of Literature in the language classroom - Lozano Huaman, Elizabeth Patricia (2022)
The objective of the research work is analysed the contributions of some researchers and in short, literature is a very useful tool or resource for learning a language, since it is an opportunity for students to benefit from various aspects such as culture because the literature is the essence of a nation at a given time, structural because in it we place linguistic and gramatical contento f a language, educational for which students practice values, universal since literature is anywhere in the world, authentic because each autor expresses their emotions and beliefs, also encourages creativity in students by using their imagination to create literature, develops the four basic competencies and interpretative skills in students. In addition the use of literature in the language classroom offers us a wide variety of literary works and genres that allow students to feel interested when reading a literary work. There are literary genres such as novels, stories, drama, fairy tale, fable, poetry which manage to attract the attention of the students since everything will depend on the age, level , sociocultural and emotional context of the students. Notably, the role of teacher is important since he plays a role of facilator, so a good selection of literary genres and a goog planning can result in a positive experience for students and teachers. Therefore, the use of basic and complementary strategies presented in this research allows teachers to plan an enriching class using literature as a learning tool. Ultimately, the goa lof using literature as a learnig tool is not to analyse literature itself, but rather to use literature as a means for students to feel interested in reading and learning at the same time.